2013
DOI: 10.1007/s10714-013-1514-0
|View full text |Cite
|
Sign up to set email alerts
|

On the static Lovelock black holes

Abstract: We consider static spherically symmetric Lovelock black holes and generalize the dimensionally continued black holes in such a way that they asymptotically for large r go over to the d-dimensional Schwarzschild black hole in dS/AdS spacetime. This means that the master algebraic polynomial is not degenerate but instead its derivative is degenerate. This family of solutions contains an interesting class of pure Lovelock black holes which are the Nth order Lovelock Λ-vacuum solutions having the remarkable proper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 45 publications
(62 reference statements)
1
84
0
Order By: Relevance
“…For instance even though the equation is completely free from the Einstein term yet a static vacuum solution with asymptotically goes over to an Einstein-dS solution in the given dimension [11]. This is quite remarkable: that the pure Lovelock solution includes Einstein gravity asymptotically even though the equation is completely free from it.…”
Section: Gravitational Equation In Higher Dimensionsmentioning
confidence: 99%
“…For instance even though the equation is completely free from the Einstein term yet a static vacuum solution with asymptotically goes over to an Einstein-dS solution in the given dimension [11]. This is quite remarkable: that the pure Lovelock solution includes Einstein gravity asymptotically even though the equation is completely free from it.…”
Section: Gravitational Equation In Higher Dimensionsmentioning
confidence: 99%
“…In Einstein gravity potential goes as 1/r d−3 that takes the familiar 1/r form only in four dimensions and none else. In contrast, for pure Lovelock it goes as 1/r α with α = (d − 2m − 1)/m [15], and hence there exists dimension spectrum d = 3m + 1 for 1/r potential. It should be emphasized that we are interested in exact solutions of gravitational field equations, not just Newtonian limit and hence must be contrasted with earlier approaches in [30,31].…”
Section: Introductionmentioning
confidence: 96%
“…Finally pure Lovelock theories, i.e., a single term in the Lovelock polynomial, exhibit very interesting features. These include -(a) there is a close connection between pure Lovelock and dimensionally continued black holes [15,16], (b) gravity is kinematic in all critical d = 2m +1 dimensions, i.e., vacuum is pure Lovelock flat [17], (c) bound orbits exist for a given m in all 2m +1 < d < 4m +1 dimensions, in contrast, for Einstein gravity they do so only in four dimensions [18] and finally (d) equipartition of gravitational and non-gravitational energy defines location of black hole horizon [19].…”
Section: Introductionmentioning
confidence: 99%
“…EGB is the N = 2 case of the Lovelock polynomial. Vacuum solutions have been determined for Lovelock gravity in general [20][21][22] as well as for dimensionally continued [5,[23][24][25], and also for pure Lovelock black holes [26,27]. Sharma [28] showed that the limiting case of the polytropic fluid may be regarded as isothermal and is important in the study of clusters of stars.…”
Section: Introductionmentioning
confidence: 99%